PENGARUH MEDIA POP UP BOOK TERHADAP KECERDASAN VISUAL SPASIAL ANAK USIA 5-6 TAHUN DI TK AL-LATIF KECAMATAN TAMBANG KABUPATEN KAMPAR - Indarto, Wusono; ', Sansiana; ', Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the effect of pop-up book media on spatial visual intelligence of children aged 5-6 years in Kindergarten Al-Latif District Tambang Kampar regency. The population in this study that is the children of class B1 which amounted to 18 children and the sample in this study are 18 children. The method used is pre-experiment with one group pretest posttest design that is experiment conducted on one group only without any comparison group. The type of instrument used in this study is to use observation and documentation guidelines to record the activities that occurred during the treatment given. The data analysis technique is using Wilcoxon test by using SPSS Statistic Ver.23. There is a significant influence between pop-up book media and spatial visual intelligence. This can be known from the results of data analysis obtained Wilcoxon test statistics. That sign result is 0.00 <0.05. This can be interpreted that there are differences in the success rate of children's science skills before and after treatment using pop-up book media. When referenced to the value of Z then obtained Zcount results of -3.771. Pop-up book media technique gives effect of 31,7% which is in medium category.Keywords: Pop-Up Book Media, Spatial Visual Intelligence